The influence of leaders' characteristics on the relationship between leadership and knowledge management - Archanjo de Souza, Daniele Santos de Oliveira [UNESP]; Pedro Salgado, Andreia Maria [UNESP]; Marins, Fernando Augusto Silva [UNESP]; Muniz, Jorge [UNESP] (Taylor & Francis Ltd, 2020)
To identify the relationship between leadership and knowledge management (KM) reported in academic publications, a systematic review of the articles contained in the Web of Science platform from 1996 to 2019 was carried out. The information obtained clarifies the relevance of the theme and the ideas described lead to results supported by studies on the competence of the leader and organizational psychology that confirm the relationship between the constructs. The conclusion presents an agenda for future studies, in order to fill the gaps identified by the diagnosis of the research questions and with the possibility of describing, through a more detailed analysis, the characteristics of the leaders associated with the KM process that allowed to present the profile of the leader in that context. The results can contribute as a practical guide in the management of human resources, providing benefits to organizations that work with KM.
Keywords: Leadership; leadership styles and competencies; knowledge management